1966
DOI: 10.1071/bt9660257
|View full text |Cite
|
Sign up to set email alerts
|

Water stress on native vegetation during the drought of 1965

Abstract: During the first half of 1965 an unprecedented drought caused widespread wilting of native trees from southern Queensland to the New South Wales-Victorian border. The reaction of some of the native vegetation in parts of the Australian Capital Territory and Monaro Region has been studied. Rainfall from January 1 to June 30 was less than one-quarter of the normal, and by the end of March signs of water stress were apparent over a wide area. The communities most severely affected were dry sclerophyll forests, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

1968
1968
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 0 publications
2
31
0
Order By: Relevance
“…A large-scale survey of dieback in the same area of Queensland as our study indicated that individuals in the E. crebra ironbark species complex were especially susceptible to dieback during the 1990s drought while C. erythrophloia populations exhibited little stem mortality (Fensham and Holman 1999). In comparisons among species that occur in different habitats, site differences in geology, soil depth and soil type have often been suggested as factors causing interspecific differences in dieback (Pook et al 1967;Fensham and Holman 1999). Although Fensham and Holman (1999) identified some differences between canopy and sub-canopy species, there is a poorer understanding of the causes of species differences in dieback within a single site (Landsberg and Wylie 1983).…”
Section: Discussionmentioning
confidence: 93%
“…A large-scale survey of dieback in the same area of Queensland as our study indicated that individuals in the E. crebra ironbark species complex were especially susceptible to dieback during the 1990s drought while C. erythrophloia populations exhibited little stem mortality (Fensham and Holman 1999). In comparisons among species that occur in different habitats, site differences in geology, soil depth and soil type have often been suggested as factors causing interspecific differences in dieback (Pook et al 1967;Fensham and Holman 1999). Although Fensham and Holman (1999) identified some differences between canopy and sub-canopy species, there is a poorer understanding of the causes of species differences in dieback within a single site (Landsberg and Wylie 1983).…”
Section: Discussionmentioning
confidence: 93%
“…globulus has been characterized to have intermediate stomatal control of transpiration during severe water stress compared to other eucalypts and deciduous species (Pook et al, 1966;Pereira et al, 1986;Pereira de Almeida and Riekerk, 1990). E. camaldulensis is reported to exhibit strong stomatal resistance under drought conditions compared to E. globulus (White et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (e.g., Pook et al, 1966;Pereira et al, 1986;Pereira de www.elsevier.com/locate/foreco Forest Ecology and Management 201 (2004) [119][120][121][122][123][124][125][126][127][128][129] Almeida and Riekerk, 1990;Abebe, 1994;White et al, 1996;James and Bell, 2000;White et al, 2000;Burgess et al, 2001) have been conducted on the effect of drought and related subjects on Eucalyptus camaldulensis and Eucalyptus globulus under various controlled and natural environments.…”
Section: Introductionmentioning
confidence: 99%
“…Protracted dieback of drought-affected trees may result if stem boring beetles invade injured stems (Hoult 1970;Pook et al 1966). …”
Section: Appendixmentioning
confidence: 99%